2010
DOI: 10.1682/jrrd.2009.07.0105
|View full text |Cite
|
Sign up to set email alerts
|

Use of weight-bearing MRI for evaluating wheelchair cushions based on internal soft-tissue deformations under ischial tuberosities

Abstract: Abstract-Deep tissue injury (DTI) is a severe type of pressure ulcer, in which damage initiates under intact skin, in soft tissues that are mechanically deformed by load-bearing bony prominences. Sitting-acquired DTI typically occurs in the gluteus muscles that could sustain deformations by the weightbearing ischial tuberosities (ITs). No clinical method currently exists for measuring internal tissue deformations; so design and selection of wheelchair cushions are based mostly on measuring sitting pressures. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In this regard, it is important to note that we surmise that 12%-strain is physiological in weightbearing fat tissues, based on several weight-bearing MRI studies performed by our group, where subjects were asked to sit in the space of an Open-MRI system, first while sitting on a rubber-tire so that their adipose tissues of the buttocks were not loaded, and next on either rigid supports or cushions. 18,19,25,26 The data collected in these studies revealed fat tissue strains in the order of 30-40% (compressive and tensile) in healthy subjects, hence 12%-strain appears to be conservative, despite appreciating that the tissue-scale (continuum) fat strains quantified by means of the MRI do not necessarily equal the cell-level strains. Moreover, multiscale finite element modeling 30 indicated that cellular strains follow the trend of continuum strains, and values could differ within a strain range of up to 15% across scales, which-when taken together with the above MRI data-demonstrates that in vivo, adipocytes in weight-bearing tissues such as the buttocks are very likely to be subjected to strains around and perhaps above 12%.…”
Section: Discussionmentioning
confidence: 86%
“…In this regard, it is important to note that we surmise that 12%-strain is physiological in weightbearing fat tissues, based on several weight-bearing MRI studies performed by our group, where subjects were asked to sit in the space of an Open-MRI system, first while sitting on a rubber-tire so that their adipose tissues of the buttocks were not loaded, and next on either rigid supports or cushions. 18,19,25,26 The data collected in these studies revealed fat tissue strains in the order of 30-40% (compressive and tensile) in healthy subjects, hence 12%-strain appears to be conservative, despite appreciating that the tissue-scale (continuum) fat strains quantified by means of the MRI do not necessarily equal the cell-level strains. Moreover, multiscale finite element modeling 30 indicated that cellular strains follow the trend of continuum strains, and values could differ within a strain range of up to 15% across scales, which-when taken together with the above MRI data-demonstrates that in vivo, adipocytes in weight-bearing tissues such as the buttocks are very likely to be subjected to strains around and perhaps above 12%.…”
Section: Discussionmentioning
confidence: 86%
“…22a, b and move forward from (a) to (c), indicating that the pressure values, contact areas, and positions might reflect characters of those postures. As the cushion type and thickness affect the peak pressure [29], this sitting pressure measurement sensor array is helpful for evaluating cushions and selecting suitable cushions for chair-bound people. Since the cushion will be further applied for monitoring wheel-chair-bound people in the prevention of pressure ulcer, pressure time integral (PTI) was also estimated.…”
Section: Accuracy Evaluation Of the Fabricated Sensing Cushionmentioning
confidence: 99%
“…One possibility is that the level of pressure relief provided by the padded floor was inadequate for the degree of immobility in this particular pig. Work by Shabshin et al 64 evaluating wheelchair cushions showed that the reduction in soft tissue deformation provided by different cushions only acts as a time buffer, delaying the onset of cell death but not eliminating it. It is possible that this time threshold for cell death was exceeded in this pig sometime during the period of paralysis.…”
Section: Dti Alters the Magnitude And Distribution Of Strain In Loadementioning
confidence: 99%